Reliability and Acceptability to Caregivers of Telehealth Administration of the Pediatric Evaluation of Disability Inventory – Computer Adaptive Test (PEDI-CAT) for Brazilian Youth with Down Syndrome. - Castilho, Julia de Souza; Barbosa, Raiane Marques Furtado; Ayupe, Kênnea Martins Almeida; Defilipo, Érica Cesário; Chagas, Paula Silva de Carvalho (Physiotherapy Canada, 2024)
Purpose: To estimate test-retest reliability of the two versions of the PEDI-CAT administered via telehealth to caregivers of Brazilian young people with DS, to compare scores on the two versions, and to determine caregiver acceptance of telehealth administration of the assessment. Method: A methodological study approved by the research ethics committee. Data collection was performed online, with a mean duration of 45.0 minutes for the content-balanced version of the PEDI-CAT and 17.5 minutes for the speedy version. Results: In total, 28 caregivers of individuals with DS up to age 21 years participated (mean = 5.9 years; SD = 4.9 years). Intra-class correlation coefficients for the four domains of the PEDI-CAT content-balanced version and four domains of the PEDI-CAT speedy version ranged from 0.77 to 0.97. There was a statistical difference between the versions in the scores of the social-cognitive domain (p < 0.05). A mean of 105 items (SD = 21) was administered in the content-balanced version and a mean of 51 items (SD = 8) in the speedy version. All the caregivers found the method of administration of the PEDI-CAT acceptable. Conclusions: This study demonstrated that either version of the Brazilian version of the PEDI-CAT can be used by telehealth in clinical practice to assess children, adolescents, and young adults with DS.